Expanding the repertoire of methanocarba nucleosides from purinergic signaling to diverse targets. Issue 11 (13th July 2021) - Jacobson, Kenneth A.; Salmaso, Veronica; Suresh, R. Rama; Tosh, Dilip K.
Abstract : Rigid methanocarba nucleotides and nucleoside bound to their protein targets (clockwise from upper left: PDB IDs 4XNW, ; 1E2L, ; 4GC7, ; 4EBD ). Abstract : Nucleoside derivatives are well represented as pharmaceuticals due to their druglike physicochemical properties, and some nucleoside drugs are designed to act on receptors. The purinergic signaling pathways for extracellular nucleosides and nucleotides, consisting of adenosine receptors, P2Y/P2X receptors for nucleotides, and enzymes such as adenosine (ribo)kinase, have been extensively studied. A general modification, i.e. a constrained, bicyclic ring system (bicyclo[3.1.0]hexane, also called methanocarba) substituted in place of a furanose ring, can increase nucleoside/nucleotide potency and/or selectivity at purinergic and antiviral targets and in interactions at diverse and unconventional targets. Compared to other common drug discovery scaffolds containing planar rings, methanocarba nucleosides display greater sp3 character ( i.e. more favorable as drug-like molecules) and can manifest as sterically-constrained North (N) or South (S) conformations. Initially weak, off-target interactions of (N)-methanocarba adenosine derivatives were detected as leads that were structurally optimized to enhance activity and selectivity toward target proteins that normally do not recognize nucleosides. By this approach, novel modulators for 5HT2 serotonin and κ-opioid receptors, dopamine (DAT) and ATP-binding cassette (ABC) transporters were found, and previously undetected antiviral activities were revealed. Thus, through methanocarba nucleoside synthesis, structure–activity relationships, and multi-target pharmacology, a robust purinergic receptor scaffold has been repurposed to satisfy the pharmacophoric requirements of various GPCRs, enzymes and transporters.